Descentralização federativa e plano estadual decenal de atendimento socioeducativo de Pernambuco: diagnóstico do quadro normativo subnacional enquanto fator indutor de efetivação de direitos fundamentais de adolescentes em cumprimento de medida socioeducativo de privação de liberdade. - Luz, Sara (2022)
The present work aims to analyze how socio-educational policy has been apprehended from a subnational perspective, using the Decennial Plan for Socio-educational Service as an analysis tool, which outlines the guidelines for planning, management and execution of national, state policy. , municipal and district of socio-education, in a time span of ten years. The idea is to understand how socio-educational policy has behaved within a model of cooperative federalism, which implies decentralization; and whether this decentralization has been a potentiating element in the socio-education process for adolescents in conflict with the law in Pernambuco. With regard to childhood and youth, despite legislation guaranteeing fundamental rights, violations of the rights of this public are constant, for this reason, part of the purpose of the research is to observe to what extent the decentralized management of socio-educational policy has contributed or harmed the guarantee of fundamental rights for adolescents who have committed an infraction. Therefore, a documentary analysis will be carried out, based on four milestones, the ECA, the law that establishes the SINASE, the National Decennial Plan for Socio-Educational Assistance and the Pernambuco State Decennial Plan for Socio- educational Assistance to understand which strategies are adopted by state governments and if they strategies have been effective in the care, protection and accountability of adolescents in compliance with a socio-educational measure of deprivation of liberty.